Long-term outcomes with pimavanserin for psychosis in clinical practice - Umer Akbar; Joseph H. Friedman (Clinical Parkinsonism & Related Disorders, 2022)
Introduction: Pimavanserin is the only medication FDA-approved for the treatment of Parkinson disease (PD) psychosis (PDP), but reports of long-term, real-world clinical experience are lacking. Methods: A retrospective chart review of all patients treated with pimavanserin was conducted at our large Movement Disorders practice in Providence, Rhode Island, USA. Demographic and clinical data for each patient were collected and descriptive analyses were performed. Results: We identified 54 patients (23 female) who initiated pimavanserin, whose median age was 70 years (range 44–87 years) and the median duration of pimavanserin therapy was 26 weeks. Initial improvement was seen in 47% of the entire group, and 50% of the DLB patients. Additional antipsychotic medication was needed concomitantly with pimavanserin to maintain a positive response for 40% of patients. Only 15% of the entire group had effective treatment of their condition with pimavanserin monotherapy over a median of 52 weeks. Among the initial responders, 32% continued on pimavanserin monotherapy. Among the non-responders, the mean trial period for patients who did not improve was 27 weeks, for patients who worsened was 16 weeks, and for those who experienced adverse effects was 1–2 weeks. Reported sex was similar across responders (60%), non-responders (56%), and the overall cohort (57%). Conclusion: Our real-world experience shows that pimavanserin is safe and tolerable, with a lower response rate than reported in other publications. While it has been proven to be effective in short-duration clinical trials, our clinical experiences, however, demonstrate less promising results in the long term.